Metabolic interactions of benzodiazepines with oxycodone ex vivo and toxicity depending on usage patterns in an animal model - Lawson, Roland; Čechová, Petra; Zarrouk, Eliès; Javellaud, James; Bazgier, Václav; Otyepka, Michal; Trouillas, Patrick; Picard, Nicolas; Marquet, Pierre; Saint-Marcoux, Franck; El Balkhi, Souleiman (British journal of pharmacology, 2023)
BACKGROUND AND PURPOSE: Opioids and benzodiazepines are frequently combined in medical as well as in non-medical contexts. At high doses, such combinations often result in serious health complications attributed to pharmacodynamics interactions. Here, we investigate the contribution of the metabolic interactions between oxycodone, diazepam and diclazepam (a designer benzodiazepine) in abuse/overdose conditions through ex vivo, in vivo and in silico approaches. EXPERIMENTAL APPROACH: A preparation of pooled human liver microsomes was used to study oxycodone metabolism in the presence or absence of diazepam or diclazepam. In mice, diazepam or diclazepam was concomitantly administered with oxycodone to mimic acute intoxication. Diclazepam was introduced on Day 10 in mice continuously infused with oxycodone for 15 days to mimic chronic intoxication. In silico modelling was used to study the molecular interactions of the three drugs with CYP3A4 and 2D6. KEY RESULTS: In mice, in acute conditions, both diazepam and diclazepam inhibited the metabolism of oxycodone. In chronic conditions and at pharmacologically equivalent doses, diclazepam drastically enhanced the production of oxymorphone. In silico, the affinity of benzodiazepines was higher than oxycodone for CYP3A4, inhibiting oxycodone metabolism through CYP3A4. Oxycodone metabolism is likely to be diverted towards CYP2D6. CONCLUSION AND IMPLICATIONS: Acute doses of diazepam or diclazepam result in the accumulation of oxycodone, whereas chronic administration induces the accumulation of oxymorphone, the toxic metabolite. This suggests that overdoses of opioids in the presence of benzodiazepines are partly due to metabolic interactions, which in turn explain the patterns of toxicity dependent on usage. LINKED ARTICLES: This article is part of a themed issue on Advances in Opioid Pharmacology at the Time of the Opioid Epidemic. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v180.7/issuetoc.
Keywords: benzodiazepines; myši; modely u zvířat; oxykodon; Diazepam; Benzodiazepines; Oxycodone; Humans; benzodiazepiny; lidé; Drug Overdose; metabolic interactions; předávkování léky; oxymorfon; designer benzodiazepines; Oxymorphone; cytochrom P-450 CYP3A; opioidní analgetika; opioids; Animals; Analgesics, Opioid; Mice; zvířata; Cytochrome P-450 CYP3A; Models, Animal; oxycodone; diazepam; diclazepam